Integrating Genomics into Health Information Systems - Martin-Sanchez, F.; Maojo, V.; Lopez-Campos, G. (Methods of Information in Medicine, 2002)
Objective: To outline the main issues related to the impact of the data generated by the Human Genome Project on health information systems. A major challenge for medical informatics is identified, consisting of adapting traditional systems to new genetic-based diagnostic and therapeutic tools. Methods: Reviewing and analysing the different health information levels from an organisational complexity point of view. A model is proposed to explain the interactions between health informatics, bioinformatics and molecular medicine.Results: We suggest a new framework that integrates genetic data into health information systems. Using this model, new topics for future research and development are identified.Conclusions: We are witnessing the birth of a new era (post-genomics). In this era technological advancements in genomics offer new opportunities for clinical applications. Medical informaticians should play an important role in this new endeavour.
Keywords: Health informatics; bioinformatics; medical informatics; genomics; genetic information